Beyond the Desk: The Everyday Managerial Practices of Executive Directors in Local Government Authorities - Igulu, George Romanus (Journal of Policy and Leadership, 2025)
This study examines the managerial roles and daily practices of Executive Directors in Local government Authorities (LGAs), drawing on self-reported responsibilities and observational insights into their everyday routines. The research employed a mixed-methods approach involving surveys, interviews, and observations to explore both the formal roles and the lived experiences of the directors. Surveys were administered to 184 LGAs, garnering 83 responses (77 complete) through simple random sampling techniques, focusing on six role categories: interpersonal, informational, decisional, operational, strategic, and diplomatic. Role performance was assessed using a structured questionnaire developed from theoretical models of managerial behaviour. To complement the survey findings, eight in-depth case studies (three urban and five district LGAs) were conducted, selected based on the performance and tenure of the directors. Data collection included semi-structured interviews, as well as direct observations of council management team meetings. Qualitative data were transcribed and analysed thematically, while quantitative data were processed using SPSS to produce descriptive statistics and reliability tests. Findings indicate that executive directors perceive nearly all managerial roles as central to their work, although variations emerge in the degree of emphasis placed on these roles. In practice, their work clusters around four key activities: administrative coordination, citizen engagement, project monitoring, and departmental supervision. The study highlights a disconnection between formally perceived roles and actual practices, illustrating that contextual demands, local expectations, and individual discretion shape managerial work. These insights contribute to a nuanced understanding of public sector leadership in decentralised governance systems.